The (fictional) autobiographical subject in push. by Sapphire - Investigating precious’s narrating I and narrated I’s: an outsider’s or an insider’s life story? - Ayres Franco de Araujo, Lana Beth (WEB REVISTA LINGUAGEM, EDUCAÇÃO E MEMÓRIA, 2019)
The present essay aims at analyzing the autobiographical subject conceived by the American writer Sapphire in her novel Push. It is taken into consideration here the fact that, in an autobiographical text, whether or not it is fictional, the subject who talks about himself is a kaleidoscopical being. It then means that the individual who writes is not, under any circumstance, the one who is written about. Therefore, it is the purpose of this paper to investigate not only the subject who weaves his life narrative, but also the objects of the narrative: the many stages of the narrator/character depicted in her bildungsroman. Making use of a deliberately misspelled text, Sapphire engenders the fictional autobiography of a girl who fights to acquire literacy and sees in education her only chance to get rid of an oppressive domestic environment. By putting a pen in Precious’s hand, Sapphire is granting her narrator/character the right to speak not only about herself but also for herself. The real author is then providing the fictional one with the prerogative of representing herself. In short, this paper focuses on revealing the Precious who narrates and the other Precious who are narrated and, in doing so, verify the gap there is between the narrator/character and those who are rescued from the past by memory and textually reconstructed. In order to do so, critical works by Sidonie Smith and Julia Watson, Susan Friedman, José Luiz Fiorin, Leigh Gilmore, among others, were used as theoretical support for the current analysis.